Abdominal Ultrasound Education for Gastroenterology Residents and Fellows - Young Koog Cheon; Youngjung Kim; Joon Seong Lee (The Korean Journal of Gastroenterology, 2022)
Ultrasound (US) is an essential diagnostic tool in almost every medical area. Therefore, abdominal US education for internal medicine residents was mandated by the Korean Association of Internal Medicine. However, US education for physicians has been conducted only in some university hospitals that directly perform abdominal US examinations in internal medicine, or some education is provided with the help of radiologists. US technology continues to become increasingly widespread, portable, and miniaturized. Furthermore, point-of-care US, i.e., US executed at the patient’s bedside to obtain real-time objective information with diagnostic and clinical monitoring purposes or to guide invasive procedures, has been incorporated in many specialties. Despite the increasing role of US, there is no systemized abdominal US education program. Therefore, the authors are trying to develop a structured abdominal US education program through cooperation with related US organizations.